Integration of Digital Technology in Islamic Religious Education Learning: A Qualitative Study on Teachers’ Competence and Implementation Models in Secondary Schools - Mintasih, Diyah; Sukiman, Sukiman; Purnama, Sigit (Jurnal Pendidikan Islam, 2024)
Purpose – The advancement of digital technology has significantly transformed the field of education, including Islamic Religious Education (PAI) learning. In Indonesia, the increasing number of internet users and the adoption of technological devices reflect a broad digital transformation. The Merdeka Belajar program demonstrates the government's commitment to digitizing education, including PAI. However, in rural areas such as Gunungkidul Regency, integrating technology into PAI learning still faces challenges, such as limited infrastructure readiness and teachers’ digital competence. Therefore, this study aims to identify the level of digital technology utilization in PAI learning, evaluate teachers’ digital competence, analyze the impact of technology integration on learning effectiveness, and develop a digital technology integration model relevant to the local context. Design/methods/approach – This study employs a qualitative approach with a descriptive method. Data were collected through observation, in-depth interviews, documentation, and surveys involving 30 PAI teachers from 19 senior high schools (SMA) in Gunungkidul Regency, selected using a purposive sampling technique. The analysis is based on the Technology Acceptance Model (TAM) and Technological, Pedagogical, and Content Knowledge (TPACK) frameworks to understand technology acceptance and teachers’ digital competence. Findings – The findings indicate that the utilization of digital technology in PAI learning is relatively widespread, with platforms such as Google Classroom, Moodle, and Edmodo being used. However, there are still gaps in infrastructure and teachers’ digital competence, particularly in creating interactive digital content. Most teachers still rely on simple presentation media and have not fully optimized technology for innovative learning. The integration of technology has been proven to enhance accessibility and interactivity in learning; however, it also poses challenges such as students’ dependency on technology and the limited training opportunities for teachers. To address these challenges, this study proposes a technology integration model that focuses on improving teachers’ digital competence, ensuring equitable infrastructure distribution, developing digital content, and implementing a hybrid learning model. Research implications – The findings provide recommendations for teachers, policymakers, and educational institutions to enhance the effectiveness of digital-based PAI learning. Several strategic steps are proposed, including intensive training for teachers in digital content creation, equalizing access to technology in remote areas, and implementing a hybrid learning model that combines conventional methods with digital technology. Furthermore, improving students’ digital literacy is also a crucial step to ensure that the integration of technology in PAI learning goes beyond mere accessibility and fosters a deeper understanding of Islamic values.